Hukum Jual Beli Semut Jepang Menurut Pandangan Ulama Nahdlatul Ulama (NU) Ponorogo - Siti Safinaturrohmah (Civiliza Publishing, 2023)
The study of fiqh from time to time continues to change and develop, including in terms of mu'amalah, mu'amalah is a part of Islamic law because mu'amalah is a matter that regulates relations between humans in society with regard to buying and selling while maintaining religion, ancestry and treasure. But everything that is done by humans must have the essence of maslahah contained in it, such as buying and selling Japanese ants which are used for medicine. Japanese ants are considered to contain many harmful side effects so they contain a lot of mafsadat. As for the preparation of this thesis, what the writer wants to achieve is to find out 1) what is the view of the Ponorogo Nahdlatul Ulama (NU) Ulama on the issue of buying and selling Japanese ants?, 2) What legal basis is used by the Ponorogo Nahdlatul Ulama (NU) Ulama in punishing the sale and purchase of ants Japan?. In this study the authors conducted field research. Researchers in extracting field data are using a qualitative approach, and analysis with an inductive method, namely examining facts and data that are specific and ending with general conclusions. To manage data, the authors use editing, organizing, and finding results. The results of this study concluded: Nahdlatul Ulama (NU) Ponorogo scholars differed in convicting the buying and selling of Japanese ants, some said it was permissible or legal and some said it was not permissible or illegal. The reason for its permissibility is because there are maslahahs and it fulfills the conditions and pillars of buying and selling. The reasons for its inadmissibility are that there are harm or problems in terms of its usefulness, Japanese ants do not have clarity about their benefits, the medical team (Indonesian Doctors Association) also does not issue research results regarding the benefits of Japanese ants for certain diseases, so this benefit is just a myth from society or from unscrupulous individuals. which creates new business opportunities for the sake of creating large profits. Meanwhile, the legal basis used by Nahdlatul Ulama (NU) Ponorogo scholars is different, and results in different decisions.